Mind, Cognition, and Neuroscience : A Philosophical Introduction - Benjamin D. Young, Carolyn Dicey Jennings (New York Routledge, 2022)
Office of Academic Affairs
MIR No: 170
Order Date: 2024-08-29
Order No: CU/OPEX/LIBRARY/30/2024-25
Received Date: 2024-09-25
Keywords: Philosophy, Humankind, Mind, Consciousness